Determinants and level of corporate sustainability disclosure on employees in Malaysia - Ozigi, Obeitoh; Mohd Said, Ridzwana; Mat Daud, Zaidi (IJECM Pub UK, 2017)
The purpose of this study is to examine the level of employee disclosure and factors that determine such disclosure. The study covers a six year period of 2010 to 2015 of 253 companies in Malaysia. This study employs two-step system generalized method of moment (GMM) for analysis. The findings reveal a low level of corporate sustainability disclosure on employee in Malaysia which is consistent with previous studies. The findings reveal that company size and age are strong determinants of employee disclosure which are consistent with previous studies; multiple directorships appear to be insignificant with employee disclosure. The study establishes the need for government involvement to enhance disclosure as voluntary disclosure appears to be inadequate to achieve the desired result as evidence shows that countries where disclosure is compulsory have high disclosure compare to countries with voluntary disclosure. This underscores the need for Malaysian Stock Exchange to come up with corporate sustainability disclosure guidelines on employees.